One-Pot Synthesis of SnO2/CNT Composite Anode Combined with Nickel Foam as a Current Collector for Lithium Ion Batteries - Zhang, Guoqing; Yang, Chengzhao; Zhang, Lei; Ma, Li (Asian Journal of Chemistry, 2012)
SnO2/carbon nanotube (CNT) composites were prepared by a simple liquid-phase precipitation and subsequent heat treatment at 350 ºC. The samples were characterized by scanning electron microscopy, X-ray diffraction. The electrochemical measurements indicate that the high SnO2 content composite using nickel foam as a conductive collector displays the best electrochemical performance with the specific capacity of 481 mAh g-1 after 30 cycles at a current density of 200 mA g-1 as anode for lithium ion batteries. This can be ascribed to the cushion effect of carbon nanotube and connection enhancement between the active material and conductive collector.